Functional characterization of CYP96T1-like cytochrome P450 from Lycoris aurea catalyzing para-para′ and para-ortho′ oxidative coupling in Amaryllidaceae alkaloids biosynthesis - Liu, Zhengtai; Sun, Bin; Li, Junde; Xiang, Yiyu; Wang, Rong; Jiang, Xiaoran; Zhu, Xinning; Xu, Sheng; Wang, Ren (Frontiers in Plant Science, 2024)
Amaryllidaceae alkaloids (AAs) are complex plant secondary metabolites possessing a wide range of biological activities. 4′-O-methylnorbelladine (4OMN) is the branchpoint intermediate for the entire AAs, and was the last common intermediate before AA pathway branches diverge. The cyclization of 4OMN by C-C oxidative coupling, which can afford para-para′, ortho-para′, and para-ortho′ scaffold, was catalyzed by cytochrome P450 96T (CYP96T) family enzymes. To clarify the mechanisms involved in this controversial step, four CYP96T homologs (LauCYP96T1, LauCYP96T1-like-1, LauCYP96T1-like-2 and LauCYP96T1-like-3) were cloned from the full-length transcriptome of Lycoris aurea. All the four LauCYP96T are localized to endoplasmic reticulum. Functional analysis reveals that LauCYP96T1 and LauCYP96T1-like proteins display inverted regioselectivity for oxidative coupling of 4OMN, in which LauCYP96T1 and LauCYP96T1-like-2 dominantly affords para-para′ scaffold, and LauCYP96T1-like-1 and LauCYP96T1-like-3 is responsible for para-ortho′ scaffold formation. Using molecular homology modeling and docking studies, we predicted models for the binding of 4OMN to LauCYP96T, and identified two amino acid residues that might be responsible for the dominant changes in generated products of para-ortho′ and para-para′ oxidative couple. Our results highlight the functional diversity and promiscuity of LauCYP96T enzymes and might provide valuable information for Amaryllidaceae alkaloid production.